Intergroup relations and strategies of minorities - Alexandre, J.; Rosa, M.; Waldzus, S. (The social developmental construction of violence and intergroup conflict, 2016)
This chapter addresses how asymmetric status positions work out in intergroup relations. In particular, the chapter focuses on one of the possible ways in which disadvantaged groups can deal with their situation: Social creativity. This chapter introduces social identity theory, which is fundamental for the understanding of asymmetric intergroup relations. Much in line with Tajfel’s thinking, in a study on children from different ethnic backgrounds the authors present evidence how under some circumstances social creativity can contribute to the upholding of the status quo. The authors also present empirical results from several studies in which they demonstrate how minorities are able to hold views on social reality, particularly on more inclusive superordinate categories, that are specifically, and very systematically distinct from the views held by their dominant majority outgroups. With that they provide evidence for the so far neglected emancipative potential of social creativity in studies with members of ethnic minorities in Portugal, with members of a strong belief minority (Evangelic Protestants in Portugal), and one study with people from two regions, Lisbon and Porto, the latter the allegedly “rival” of Lisbon. They claim that—compared to the alternative strategy of open social competition with the powerful outgroup—social creativity has been underestimated as a strategy of social change.